2019
DOI: 10.1016/j.invent.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Web-based indicated prevention of common mental disorders in university students in four European countries – Study protocol for a randomised controlled trial

Abstract: BackgroundMental disorders and their symptoms are highly prevalent in the university student population, and the transition from secondary to tertiary education is associated with a rise in mental health problems. Existing web-based interventions for the prevention of common mental disorders in student populations often focus on just one disorder and have not been designed specifically for students. There is thus a need for transdiagnostic, student-specific preventative interventions that can be widely dissemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 53 publications
(59 reference statements)
1
16
0
1
Order By: Relevance
“…Recent studies have shown great progress with the use of online support systems as interactive interventions, demonstrating their positive impact on accessibility and their flexibility [38, 39]. Furthermore, effects have been shown to be longitudinal, with self-reported symptoms significantly reduced 12 months post participation [40, 41].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown great progress with the use of online support systems as interactive interventions, demonstrating their positive impact on accessibility and their flexibility [38, 39]. Furthermore, effects have been shown to be longitudinal, with self-reported symptoms significantly reduced 12 months post participation [40, 41].…”
Section: Introductionmentioning
confidence: 99%
“…Jones Bell et al (2018) describe the study protocol of an RCT conducted in Austria and Spain, evaluating unguided or mobile-based prevention of eating disorders and obesity in adolescents in school settings. Musiat et al (2018) present the study protocol of a randomized controlled prevention trial. The focus of this trial is on personality traits as a risk factor for common mental health disorders in university students from UK, Austria and Germany.…”
Section: Overall Structure Of Icare Consortiummentioning
confidence: 99%
“…During the planning phase, we defined the research hypotheses, selected the most appropriate outcome parameters, formulated statistical (null) hypotheses to prove the primary research questions, selected statistical test procedures and performed power calculations to determine the necessary sample sizes. For the details of each study please see the individual study protocols (Vollert et al, 2018; Nacke et al, 2018; Herrero et al, 2018; Weisel et al, 2018; Jones Bell et al, 2018; Musiat et al, 2018; Spencer et al, 2018). ICare trials target a variety of primary outcomes, such as short-term effects (e.g., reduction of scores at post-measurement), long-term effects (e.g., reduction of target scores at follow-up measurements).…”
Section: Study Designsmentioning
confidence: 99%
“…Effect size estimates are based on published literature. For details on the study specific effect size estimates and power calculations please see the individual study protocols (Vollert et al, 2018; Nacke et al, 2018; Herrero et al, 2018; Weisel et al, 2018; Jones Bell et al, 2018; Musiat et al, 2018; Spencer et al, 2018). Sample sizes were calculated using the following software: G*Power (Faul et al, 2007), PASS (Hintze, 2014; PASS 13.…”
Section: Planned Statistical Analysesmentioning
confidence: 99%